Sports Tourism as a Component of Russian Socio-Cultural Modernisation - ARTKUHOV, Andrey V.; KIBENKO, Valeriy A.; REBYSHEVA, Lydia V. (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019, 2019)
One of the areas that affect the state of health is an active-sporting lifestyle, which is of particular importance for people of young age. To promote the health of students, the article proposes the development of methods for managing complex coordination movements in space using physical education methods at physical education and sports classes. As a result, this scientific article has developed a system of special exercises for physical and psychological training of students. It is proposed to include in the pedagogical process special control actions for the development of physical and psychological stability, active exercises and other means. This set of exercises provides a significantly large increase in indicators of physical fitness of students, which was proven experimentally. As one of the methods of improving the health of students, sports tourism is considered in detail, highlighting its advantages in comparison with other sports. It is concluded that the introduction of a developed system of physical exercises and sports tourism in higher education institutions contributes to improving health, improving efficiency and physical fitness of students.